Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve the given system of linear equations:
[tex]\[ \begin{cases} 3x - 2y = -2 \\ 5x + 8y = -80 \end{cases} \][/tex]
we can follow these steps:
### Step 1: Write both equations in standard form.
The given system is already in standard form:
1. [tex]\(3x - 2y = -2\)[/tex]
2. [tex]\(5x + 8y = -80\)[/tex]
### Step 2: Solve one of the equations for one variable in terms of the other variable.
Let's solve the first equation for [tex]\(x\)[/tex]:
[tex]\[ 3x - 2y = -2 \][/tex]
Add [tex]\(2y\)[/tex] to both sides:
[tex]\[ 3x = 2y - 2 \][/tex]
Divide both sides by 3:
[tex]\[ x = \frac{2y - 2}{3} \][/tex]
### Step 3: Substitute this expression into the second equation.
We substitute [tex]\(x = \frac{2y - 2}{3}\)[/tex] into the second equation [tex]\(5x + 8y = -80\)[/tex]:
[tex]\[ 5 \left( \frac{2y - 2}{3} \right) + 8y = -80 \][/tex]
Multiply both sides by 3 to clear the fraction:
[tex]\[ 5(2y - 2) + 24y = -240 \][/tex]
Distribute the 5:
[tex]\[ 10y - 10 + 24y = -240 \][/tex]
Combine like terms:
[tex]\[ 34y - 10 = -240 \][/tex]
### Step 4: Solve for [tex]\(y\)[/tex].
Add 10 to both sides:
[tex]\[ 34y = -230 \][/tex]
Divide both sides by 34:
[tex]\[ y = \frac{-230}{34} = -\frac{115}{17} \][/tex]
### Step 5: Substitute the value of [tex]\(y\)[/tex] back into the expression for [tex]\(x\)[/tex].
Now substitute [tex]\(y = -\frac{115}{17}\)[/tex] back into the expression [tex]\(x = \frac{2y - 2}{3}\)[/tex]:
[tex]\[ x = \frac{2\left(-\frac{115}{17}\right) - 2}{3} \][/tex]
Simplify the expression inside the parenthesis:
[tex]\[ x = \frac{-\frac{230}{17} - 2}{3} \][/tex]
Convert the -2 to a common denominator with 17:
[tex]\[ x = \frac{-\frac{230}{17} - \frac{34}{17}}{3} \][/tex]
Combine the fractions:
[tex]\[ x = \frac{-\frac{264}{17}}{3} \][/tex]
Divide by 3:
[tex]\[ x = \frac{-264}{17 \cdot 3} = \frac{-264}{51} = -\frac{88}{17} \][/tex]
### Step 6: Verify the solutions.
To ensure our solutions are correct, substitute [tex]\(x = -\frac{88}{17}\)[/tex] and [tex]\(y = -\frac{115}{17}\)[/tex] back into both original equations to verify:
1. For [tex]\(3x - 2y = -2\)[/tex]:
[tex]\[ 3 \left( -\frac{88}{17} \right) - 2 \left( -\frac{115}{17} \right) = -\frac{264}{17} + \frac{230}{17} = -\frac{34}{17} = -2 \][/tex]
2. For [tex]\(5x + 8y = -80\)[/tex]:
[tex]\[ 5 \left( -\frac{88}{17} \right) + 8 \left( -\frac{115}{17} \right) = -\frac{440}{17} - \frac{920}{17} = -\frac{1360}{17} = -80 \][/tex]
Both equations are satisfied, confirming our solutions.
### Solution:
[tex]\[ x = -\frac{88}{17}, \quad y = -\frac{115}{17} \][/tex]
[tex]\[ \begin{cases} 3x - 2y = -2 \\ 5x + 8y = -80 \end{cases} \][/tex]
we can follow these steps:
### Step 1: Write both equations in standard form.
The given system is already in standard form:
1. [tex]\(3x - 2y = -2\)[/tex]
2. [tex]\(5x + 8y = -80\)[/tex]
### Step 2: Solve one of the equations for one variable in terms of the other variable.
Let's solve the first equation for [tex]\(x\)[/tex]:
[tex]\[ 3x - 2y = -2 \][/tex]
Add [tex]\(2y\)[/tex] to both sides:
[tex]\[ 3x = 2y - 2 \][/tex]
Divide both sides by 3:
[tex]\[ x = \frac{2y - 2}{3} \][/tex]
### Step 3: Substitute this expression into the second equation.
We substitute [tex]\(x = \frac{2y - 2}{3}\)[/tex] into the second equation [tex]\(5x + 8y = -80\)[/tex]:
[tex]\[ 5 \left( \frac{2y - 2}{3} \right) + 8y = -80 \][/tex]
Multiply both sides by 3 to clear the fraction:
[tex]\[ 5(2y - 2) + 24y = -240 \][/tex]
Distribute the 5:
[tex]\[ 10y - 10 + 24y = -240 \][/tex]
Combine like terms:
[tex]\[ 34y - 10 = -240 \][/tex]
### Step 4: Solve for [tex]\(y\)[/tex].
Add 10 to both sides:
[tex]\[ 34y = -230 \][/tex]
Divide both sides by 34:
[tex]\[ y = \frac{-230}{34} = -\frac{115}{17} \][/tex]
### Step 5: Substitute the value of [tex]\(y\)[/tex] back into the expression for [tex]\(x\)[/tex].
Now substitute [tex]\(y = -\frac{115}{17}\)[/tex] back into the expression [tex]\(x = \frac{2y - 2}{3}\)[/tex]:
[tex]\[ x = \frac{2\left(-\frac{115}{17}\right) - 2}{3} \][/tex]
Simplify the expression inside the parenthesis:
[tex]\[ x = \frac{-\frac{230}{17} - 2}{3} \][/tex]
Convert the -2 to a common denominator with 17:
[tex]\[ x = \frac{-\frac{230}{17} - \frac{34}{17}}{3} \][/tex]
Combine the fractions:
[tex]\[ x = \frac{-\frac{264}{17}}{3} \][/tex]
Divide by 3:
[tex]\[ x = \frac{-264}{17 \cdot 3} = \frac{-264}{51} = -\frac{88}{17} \][/tex]
### Step 6: Verify the solutions.
To ensure our solutions are correct, substitute [tex]\(x = -\frac{88}{17}\)[/tex] and [tex]\(y = -\frac{115}{17}\)[/tex] back into both original equations to verify:
1. For [tex]\(3x - 2y = -2\)[/tex]:
[tex]\[ 3 \left( -\frac{88}{17} \right) - 2 \left( -\frac{115}{17} \right) = -\frac{264}{17} + \frac{230}{17} = -\frac{34}{17} = -2 \][/tex]
2. For [tex]\(5x + 8y = -80\)[/tex]:
[tex]\[ 5 \left( -\frac{88}{17} \right) + 8 \left( -\frac{115}{17} \right) = -\frac{440}{17} - \frac{920}{17} = -\frac{1360}{17} = -80 \][/tex]
Both equations are satisfied, confirming our solutions.
### Solution:
[tex]\[ x = -\frac{88}{17}, \quad y = -\frac{115}{17} \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.